ASSESSING LEGAL CERTAINTY IN SENTENCING AGGRAVATION IN THE DECISION OF THE CENTRAL JAKARTA DISTRICT - Natashya, Jasmine; Adhari, Ade (Sekolah Tinggi Ilmu Hukum Awang Long, 2025)
One crime that cannot be avoided is violence. Joint criminal acts of violence as regulated in Article 170 of the Criminal Code often result in serious injury and can even cause death to the victim. This study analyzes the application of aggravated punishment in the Central Jakarta District Court Decision No. 200/Pid.B/2025/Pn.Jkt.Pst through the effects of the perpetrator's use of acid, which caused third-degree burns covering 4.5% of the total surface area of the victim's face. The research method used by the author is normative legal research using a legislative approach to examine laws and regulations. The result of the research on Central Jakarta District Court Decision No. 200/Pid.B/2025/Pn.Jkt.Pst is that the sentence imposed was one year and two months in prison, far below the maximum penalty of nine years specified in the Criminal Code. This condition shows an imbalance between the severity of the consequences and the lightness of the punishment, which ultimately causes legal uncertainty in the application of Article 170 of the Criminal Code.